A Data Analysis Graphical User Interface for RoboCup 2D Soccer Simulation League - Pereira, Felipe; Soares, Mateus; Barros, Edna (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Spatial and temporal data from a robotics soccer game could enable an in-depth analysis of the game. However, the amount and nature of the data make it challenging for analysts to uncover insights from it. This paper presents a user experience-oriented approach that aims to solve a data visualization problem in the context of RoboCup Soccer 2D Simulation League matches. At each cycle of a match, a set of data containing information about the ball, players, and overall game status is provided by the server and later compiled into a dense log file. This log file is a highly valuable resource for understanding the performance of both teams in a given match. However, the considerable amount of data in a raw format makes it challenging to gather and interpret useful information by manual means. In this sense, we propose a data analysis tool that, through the use of data manipulation and data visualization libraries, offers a graphical interface from which the user can get refined information such as statistics and performance diagnoses directly from a specific log file, allowing more in-depth understanding and accurate observations on both teams play actions.